1974
DOI: 10.1017/s0021859600051972
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of berseem hay by ruminants

Abstract: SUMMARYFour young females of four ruminant species, namely cow, buffalo, sheep and goat were used to study the utilization of sun-cured berseem hay (20·6% CP) fed in long form during a 28-day experimental period. Voluntary intake of hay was estimated during the last 10 days and digestibility of feed nutrients and nitrogen balance during the last 6 days.The digestibility coefficients of dry matter (D.M.), organic matter (OM), crude protein (CP), crude fibre (CF), ether extract (EE) and nitrogen-free extract wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Buffaloes are thus able to utilize the low-grade roughages better than the other species. In an earlier investigation with the same four ruminant species fed free choice with a high-quality berseem hay (Sharma & Murdia, 1974), similar TDN intakes based upon metabolic body size were obtained, even though D.M. intake differed as between larger and smaller ruminant species.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Buffaloes are thus able to utilize the low-grade roughages better than the other species. In an earlier investigation with the same four ruminant species fed free choice with a high-quality berseem hay (Sharma & Murdia, 1974), similar TDN intakes based upon metabolic body size were obtained, even though D.M. intake differed as between larger and smaller ruminant species.…”
Section: Resultsmentioning
confidence: 54%
“…When the four species eat the same lowgrade feed to capacity, the digestive powers of goats appear to be superior to the other three species, of sheep marginally better than buffaloes and of buffaloes superior to cows. The four species ranked in similar order when their ability to digest feed nutrients of a high-grade roughage, berseem hay (21-2% CP), was investigated earlier (Sharma & Murdia, 1974). Watson et al (1948), and Blaxter et al (1966), on the other hand, reported slightly higher digestibility of the feed nutrients of low-grade roughages for cattle than for sheep.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, high protein levels in the diet cause unbalance with more available ammonia in the rumen, which can increase UC (Sucak et al, 2017). In our study, high UC during the winter and spring were probably due to the greater availability of Berseem grass (Trifolium alexandrinum) high in protein mainly soluble (15-25 % DM according to Sharma and Murdia (1974)), which is very frequent at this period of the year in Tunisia. Seasonal changes affected also milk lactose content.…”
Section: Effect Of Seasonsmentioning
confidence: 56%
“…Berseem is the most dominant winter season forage crop grown in 1.9 mha area in India with a productivity of 60-110 t/ha (Anon, 2012). It provides high quality green forage which is rich in protein (15-25%), minerals (11-19%) and carotene (Sharma and Murdia, 1974). Biomass production per unit time in berseem basically depend on the photosynthetic efficiency, regeneration after each cut and enzyme system controlling source sink relationship during the vegetative growth of the crop.…”
Section: Introductionmentioning
confidence: 99%